THE VALIDITY OF SCIENCE ELECTRONIC TEACHING MATERIALS WITH THE STEAM APPROACH IN ELEMENTARY SCHOOLS - Berliany Nuragnia; Nadiroh Nadiroh; Herlina Usman (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
One of the abilities that need to be mastered by students with the rapid development of science and technology is the ability to integrate various disciplines. STEAM is one of the popular integrated learning implemented in the world of education. However, research shows that students and teachers still have difficulties in accessing teaching materials in STEAM learning. This study aims to develop science teaching materials with a STEAM approach. The research implements the development method using the 4D Thiagarajan model. Science electronic teaching materials were tested on a limited basis to 40 fifth grade elementary school students. The results showed that based on expert judgment, electronic science teaching materials with the STEAM approach that were developed were valid for use in learning in elementary schools. The percentage of eligibility by media experts shows a value of 98.61% which can be interpreted as a very feasible media. The results of the percentage of linguists' assessments show a value of 100% which is interpreted as very feasible. Meanwhile, the percentage of material experts showed a value of 81.7%. interpreted as feasible. The results of the student trial showed a percentage value of 81.28% which was interpreted as saying that the teaching materials developed were suitable for use. Therefore, it can be concluded that the science electronic teaching materials with the STEAM approach that were developed are suitable for use in elementary school learning.